2022
DOI: 10.21203/rs.3.rs-2289825/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consistency of Serial Ultrasonographic Joint Tissue Measurements by the Joint tissueActivity and Damage Exam (JADE) protocol in Relation to Hemophilic Joint Health Parameters

Abstract: Objectives The Joint tissueActivity and Damage Exam (JADE) is a point-of-care (POC) musculoskeletal ultrasound (MSKUS) protocol for non-radiologists to evaluate hemophilic arthopathy. Our aim was to determine the consistency of cross-sectional analyses of direct tissue measurements (JADE protocol) and clinical and functional joint assessments at three clinic visits. Methods We prospectively studied adults (n = 44) with hemophilia (A or B) of any severity and arthropathy at 3 North American sites. We assessed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…US detected more early joint changes (synovitis and osteochondral damage), while HJHS 2.1 showed the added value of detecting relevant physical and functional changes. [23][24][25][26][27] Another recent systematic review and meta-analysis included fifteen studies reporting on swelling at physical examination and synovial proliferation on US in 2890 joints of 627 patients concluded that joint swelling had low sensitivity for presence of US-detected synovial proliferation in haemophilia, suggesting underestimation of synovial proliferation by physical examination alone. 28 Prevalence of subclinical synovial proliferation in the reviewed studies ranged from 0% to 55%.…”
Section: Joint Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…US detected more early joint changes (synovitis and osteochondral damage), while HJHS 2.1 showed the added value of detecting relevant physical and functional changes. [23][24][25][26][27] Another recent systematic review and meta-analysis included fifteen studies reporting on swelling at physical examination and synovial proliferation on US in 2890 joints of 627 patients concluded that joint swelling had low sensitivity for presence of US-detected synovial proliferation in haemophilia, suggesting underestimation of synovial proliferation by physical examination alone. 28 Prevalence of subclinical synovial proliferation in the reviewed studies ranged from 0% to 55%.…”
Section: Joint Assessmentmentioning
confidence: 99%
“…POC-MSKUS is a safe, cost-effective, readily available, and sensitive tool that allows for accurate diagnosis of acute haemarthrosis 19,26,33,34 and serial evalua-tion of synovial proliferation (active vs. inactive) 18,28,29 and the overall condition of osteochondral surfaces of index joints in PwH. 22,26 It is crucial to point out that while early diagnosis and management of haemophilic arthropathy is becoming more relevant for clinical management and individualised patient regimens 29 evidence to conclude that US-detectable findings are sensitive to or could inform changes or intensification of prophylactic therapy in PwH remains insufficient. 23 Significant gaps in the evidence for all assessment tools remain, and these tools complement one another in painting an accurate picture of the joint status.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation